The World Bank Annual Report 2007 - World Bank (Washington, DC, 2012)
This World Bank annual report focuses on the work of the World Bank Group as it relates to countries and people striving to overcome poverty in all regions, especially in Africa. The World Bank Group is working with partners on more than 620 projects: to give both boys and girls a chance to learn; offer health services to those in need of care; promote the development of the private sector so as to put local savings to work creating jobs and property for the poor; and build infrastructure and secure, sustainable energy resources that are prerequisites for growth. This report also highlights the World Bank's work to strengthen governance, institutions, and the rule of law so people have a fair opportunity to forge a future for their families and countries. Regional perspectives are reviewed, through a breakdown of the Bank's lending and activities across the developing world, featuring highlights of projects in borrowing countries within each of the Bank's six regions. The report gives the fiscal year activities and gives a description of the Bank's development knowledge-sharing over the fiscal year 2007; a discussion of the Bank's approach to lending in low income, and middle-income countries; the Bank's resources; and a summary of the Bank's lending by region, theme, and sector, such as environmental programs and infrastructure projects. This section also describes the Bank's partnerships with public, private, and civil society stakeholders. The fiscal 2007 financial statements, organizational information, income by region, new operations approved in fiscal 2007 are given in this report.